The Consumer Rights Protection in International Digital Transactions: RCEP Implications for Indonesian Law - Hafidza Zia; Andre Zanij Deananda (University Of Bengkulu Law Journal, 2025)
The RCEP agreement was ratified by the Indonesian Parliament on August 30, 2022, covering aspects such as e-commerce and consumer protection in digital transactions. However, its implementation raises issues regarding the protection of consumer personal data and dispute resolution between parties, especially in the appointment of panels. Although Indonesian law has provisions for personal data protection, the institution responsible for supervising and handling cases has not yet been established. Additionally, the appointment of panels for dispute resolution is unclear, which may lead to future problems. While there is existing consumer protection legislation, it is outdated and not suitable for the digital era. The government needs to take an active role in protecting consumers by establishing a personal data protection agency, requesting the establishment of an RCEP Dispute Settlement Secretariat for clarity in panel appointments, and updating the Consumer Protection Law to address digitalization. These steps are essential for safeguarding the people of Indonesia.